Environmental and lifestyle factors affecting exposure to polycyclic aromatic hydrocarbons in the general population in a Middle Eastern area. (September 2018) - Hoseini, Mohammad; Nabizadeh, Ramin; Delgado-Saborit, Juana Maria; Rafiee, Ata; Yaghmaeian, Kamyar; Parmy, Saeid; Faridi, Sasan; Hassanvand, Mohammad Sadegh; Yunesian, Masud; Naddafi, Kazem
Abstract: The aim of this study was to investigate environmental and lifestyle factors affecting exposure to PAHs in the general population in a large city of the Middle East (Tehran) by measuring urinary monohydroxy polycyclic aromatic hydrocarbons (OH-PAHs) and establishing relationships between PAHs exposure and related factors. Urine samples were collected from 222 randomly chosen subjects who were living in the urban area of Tehran, Iran. Subjects were required to complete a detailed questionnaire aimed to document their personal and sociodemographic information, activities, cooking-related appliances, smoking history/exposure, and consumed foodstuff. Identification and quantification of six OH-PAHs was carried out using a gas chromatography with mass spectrometry (GC-MS). The geometric means for 1-OHP, 1-NAP, 2-NAP, 2-FLU, 9-FLU, and 9-PHE for whole population study were 310, 1220, 3070, 530, 330, and 130 ng/g creatinine, respectively. The two naphthalene metabolites contributed on average 77% of the total concentration of six measured OH-PAHs, followed by the 2-FLU, 1-OHP, 9-FLU, and 9-PHE. The most important predictors of urinary PAHs were consumption of grilled/barbecued foods, smoking, and exposure to environmental tobacco smoking. Water pipe smoking was linked to urinary OH-PAH metabolite in a dose-response function. Residential traffic was also related with OH-PAH metabolite concentrations. Other factors including gender, age, exposure to common house insecticides, open burning, and candle burning were found to be statistically associated with the urinary levels of some OH-PAHs. High exposure to PAHs among general population in Middle Eastern large cities and its associated health implications calls for public health measures to reduce PAHs exposure. Graphical abstract: Image 1 Highlights: Urinary OH-PAHs were measured in general population of a megacity. High urinary OH-PAHs levels were found in the studied population. Significant relationship was observed between the OH-PAHs and traffic density. Water pipe smoking was linked to urinary OH-PAHs in a dose-response function.